2021
DOI: 10.2991/artres.k.201225.001
|View full text |Cite
|
Sign up to set email alerts
|

Central Blood Pressure in Young Kendo Athletes: Implications of Combined Anaerobic and Strength Training

Abstract: Background:Exercise training-induced adaptation of central Blood Pressure (BP) depends on exercise mode. Kendo, a traditional Japanese martial art, is a unique exercise mode because its training encompasses anaerobic and resistance training components. However, the effects of habitual kendo training on central BP have not been established. Objective:The aim of this study was to compare the central BP of high-level kendo athletes and age-matched controls without exercise habits.Methods: Thirty-six young univers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
(23 reference statements)
0
1
0
Order By: Relevance
“…Although current athletes exhibit elevated blood pressure, this may be an adaptation to exercise training and does not influence the development of hypertension after retirement. It has been suggested that resistance and endurance training‐induced increased PP is an adaptation to the exercise training due to an increased cardiac function (Yoshioka et al, 2021 ), and the cardiovascular adaptation to the exercise training returns to the baseline levels after the detraining period (Miyachi et al, 2004 ; Mustata et al, 2004 ). In the present study, although current athletes showed higher blood pressure than the non‐athlete controls, former athletes did not exhibit a higher prevalence of hypertension than the general population.…”
Section: Discussionmentioning
confidence: 99%
“…Although current athletes exhibit elevated blood pressure, this may be an adaptation to exercise training and does not influence the development of hypertension after retirement. It has been suggested that resistance and endurance training‐induced increased PP is an adaptation to the exercise training due to an increased cardiac function (Yoshioka et al, 2021 ), and the cardiovascular adaptation to the exercise training returns to the baseline levels after the detraining period (Miyachi et al, 2004 ; Mustata et al, 2004 ). In the present study, although current athletes showed higher blood pressure than the non‐athlete controls, former athletes did not exhibit a higher prevalence of hypertension than the general population.…”
Section: Discussionmentioning
confidence: 99%